The intergenerational transmission of ethnic essentialism: how parents talk counts the most. Issue 4 (11th September 2014) - Segall, Gili; Birnbaum, Dana; Deeb, Inas; Diesendruck, Gil
Abstract The present study analyzed the role of parents as potential sources of children's essentialist beliefs about ethnicity. We tested 76 parent–child (5‐year‐olds) dyads of Jewish Israeli parents from three social groups, defined by the kindergartens children attended: national religious, secular, or Jewish‐Arab integrated. We assessed parents' and children's beliefs, and parents' usage of ethnic attitudinal and categorization markers in a book‐reading activity. Overall, national religious parents manifested the strongest ethnic essentialism and endorsement of anti‐negotiations with Palestinians, and were the most likely to express negative attitudes and mark ethnic categories in their conversations with their children. Moreover, regression analyses revealed that ethnic categorization in parents' speech was the most reliable predictor of children's ethnic essentialism. Ethnic essentialism is transmitted to children not via explicit communication of intergroup beliefs or attitudes, but rather via the sheer marking of categories in ways that resonate with children's own intuitive ways of conceptualizing the social world.